Impact of apremilast on quality of life in Behçet's syndrome: analysis of the phase 3 RELIEF study. Issue 2 (7th July 2022) - Hatemi, Gülen; Mahr, Alfred; Takeno, Mitsuhiro; Kim, Doyoung; Melikoğlu, Melike; Cheng, Sue; McCue, Shannon; Paris, Maria; Chen, Mindy; Yazici, Yusuf
Abstract : Objective: To assess apremilast's impact on patient quality of life (QoL) in active Behçet's syndrome and correlations between improvement in patients' QoL and efficacy measures in the phase 3 RELIEF study. Methods: QoL measures included Behçet's Disease QoL (BDQoL), 36-Item Short-Form Health Survey V.2 (SF-36v2) Physical/Mental Component Summary (PCS/MCS) and eight subscale scores, focusing on Physical Functioning (PF). Pearson's correlation coefficients assessed relationships between efficacy endpoints (oral ulcer count, oral ulcer pain, Behçet's Syndrome Activity Scale (BSAS), Behçet's Disease Current Activity Form (BDCAF)) and QoL endpoints for apremilast at Week 12. Results: Apremilast (n=104) demonstrated significantly greater improvements versus placebo (n=103) in SF-36v2 PCS (3.1 vs 0.9), MCS (4.6 vs ─0.7) and PF (2.9 vs 0.14), respectively (all p<0.05). Mild correlations were observed in improvements of SF-36v2 measures (PCS, MCS, PF) with oral ulcer count (r=−0.11, PCS), and change in oral ulcer pain from baseline (r=−0.28, PCS; r=−0.10, PF) and BSAS (r=−0.38, PCS; r=−0.20, PF; r=−0.16, MCS). Correlations among BDCAF and SF-36v2 components and BDQoL were variable. BDQoL showed mild/moderate correlations with SF-36v2 components (r=−0.18, PCS; r=−0.13, PF; r=−0.45, MCS). Conclusions: Apremilast was associated with significant improvements in QoL measures of SF-36v2 PCS, MCS and PF and BDQoL in patients with Behçet's syndrome. Correlations of improvement among QoL endpoints support the beneficial clinical effects of apremilast in Behçet's syndrome. Trial registration number: NCT02307513 .